Explaining the Basics and Logic of Mother Tongue Education, a Way for Educational Justice in Bilingual Primary School Students - Bahrami, Fatemeh; Ghaderi, Mostafa; Talebi, Behnam (Iranian Journal of Educational Sociology, 2022)
Purpose: The present study was conducted with the aim of explaining the principles and logic of education in the mother tongue, a way to educational justice.Methodology: The research method in this study was qualitative. The statistical population includes 14 Buddhist experts and physicians who are experts in the field of curriculum and multicultural education. The sampling method was purposeful and criterion-based and was completed after 14 theoretical saturation interviews. Schematic analysis was also used to load internal information and collect interviews. The research tool for data collection was a semi-created interview. The reliability method has been used to ensure the reliability tool. Content analysis was performed to analyse the data.Findings: Findings A total of 38 codes were extracted in the form of six main themes with the titles of formation of socio-professional identity of learner’s education, comprehensive development of students, deep learning - student’s satisfaction and academic achievement, preservation of culture, customs, traditions And ethnicities - nationalities, a tool for social equality and the preservation of cultural, economic and cultural capital are categorized as the logic of education in the mother tongue, and the necessary foundations for education in the mother tongue include the basics of budget education such as reading, writing, arithmetic and Most important is the presence of a skilled educator or teacher who weakens the potential systems that cover the training.Conclusion: Based on the research findings, the components of student’s socio-professional identity formation, all-round growth of students, deep learning - student’s satisfaction and academic achievement, preservation of culture, customs, traditions and ethnicities - nationalities, a tool for social equality and preservation The value of cultural capital as logic and the necessary foundations for education in the mother tongue included the basic principles of education